Is the agricultural industry spared from the influence of the Australian carbon tax?. (2nd December 2014) - Meng, Samuel
Abstract The Australian agricultural sector provides food security for the nation and affects the livelihood of farmers and the development of rural communities. This sector has been uneasy about the Australian carbon tax scheme introduced in July 2012 although the government has exempted the agricultural sector from the scheme. By employing a computable general equilibrium model and an environmentally extended Social Accounting Matrix, this article simulates the effects of different carbon tax policy scenarios. The modeling results show that all agricultural sectors will be affected negatively but to differing degrees. The household compensation policy will improve the performance of the poultry and fishing sectors, while having opposite effects in the other agricultural sectors. The inclusion of the agricultural industry into the carbon tax scheme will lead to a considerable further decrease in output, employment and profitability in the agricultural sector, and a significant further reduction in real GDP, but a much larger emission reduction.